Perbandingan Penggunaan Diameter Curly Iron Terhadap Hasil Penataan Rambut Bergelombang Hollywood Wave Pada Rambut Lurus - Fadilla Ramadhani; Febri Silvia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Hairstyling is a crucial aspect of enhancing one’s aesthetic appearance and self-expression, with the Hollywood Wave being one of the most iconic and classic styles. Characterized by large, shiny, and neatly arranged “S”-shaped waves, this style requires accuracy in both technique and tools. One of the most influential factors in achieving the desired look is the diameter of the curly iron used. Observations during an internship at a national television station revealed that different curly iron diameters, specifically 28 mm and 25 mm, produce varied results when applied to long straight hair. This study aims to compare the effectiveness of using 28 mm and 25 mm diameter curly irons in creating Hollywood Wave styles. The research employed a quantitative method with a One-Group Pretest-Posttest Design. The independent variable was the Hollywood Wave styling technique, while the dependent variable was the styling result measured across three indicators: wave shape, wave durability, and wave volume. The sample consisted of students who had completed the Hair Styling course and had long straight hair, selected through purposive sampling. Data were analyzed using descriptive statistics, followed by normality, homogeneity, and hypothesis testing to ensure validity. The findings demonstrate that the 28 mm curly iron performs more effectively than the 25 mm in producing Hollywood Waves that are neater, longer-lasting, and more voluminous. Statistical analysis confirms a significant difference between the two diameters in achieving optimal styling results. This suggests that the larger diameter curly iron not only provides a smoother and more polished wave pattern but also improves the durability and overall quality of the style. The study contributes to hairstyling practices by offering evidence-based insights into tool selection for professional styling, particularly for achieving the Hollywood Wave look.